The Intermediary Role of Searching for Meaning in Young Adults in the Relationship Between Loneliness and Digital Game Addiction - Küçükşen, Kübra; Budak, Hatice (Addicta: The Turkish Journal on Addictions, 2024)
Abstract: In the present study, the intermediary role of searching for meaning in the relationship between loneliness and digital game addiction in young adults was examined. The study was designed as a correlational survey and model testing using path analysisThe sampling for this study, consisted of a total of 1476 participants—of which 1152 were female and 324 were male. The “Personal Information Form,” “Game Addiction Scale,” “Meaning of Life Scale,” and “Social-Emotional Loneliness Scale” were used as the data collection tools. The results of structural equation modeling show that the data fit perfectly with the model. The model that was designed was validated. It was found that social loneliness and emotional loneliness predict the meaning and purpose of life at a negative and significant level. Also, the meaning and purpose of life predicted excessive focus and suspense, deprivation and seeking, emotional change, and contemplation at a negative and significant level. It is recommended to conduct awareness studies and value education regarding the meaning and purpose of life in the fight against digital addiction for young adults and adolescents.